TGV through hole filling method based on magnetic field assisted electrochemical deposition

Through magnetic field-assisted electrochemical deposition and gradient pulse plating technology, combined with nanostructure modification and TiN transition layer, the problems of uneven through-hole filling, bubble residue and poor adhesion in TGV technology are solved, achieving high-quality through-hole filling and more reliable packaging.

CN119800462APending Publication Date: 2025-04-11SICHUAN SHUWANG CHENSHENG NEW MATERIALS CO LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202510215264.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-26
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

In TGV technology, there are problems such as uneven through-hole filling, residual bubbles in the hole, poor metal adhesion on the side wall and limitation of ion diffusion, which affect the quality and reliability of the packaging.

Method used

The TGV through-hole filling method based on magnetic field-assisted electrochemical deposition is adopted. Through the magnetic field-assisted and gradient pulse plating process, combined with nanostructure modification and the design of TiN transition layer, the adhesion and filling quality of metal and glass hole walls are improved.

Benefits of technology

It significantly improves the filling quality of TGV through holes, reduces the void ratio, improves the reliability of the packaging, shortens the production cycle, and improves the stability of the overall structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800462A_ABST
    Figure CN119800462A_ABST
Patent Text Reader

Abstract

The invention discloses a TGV through hole filling method based on magnetic field assisted electrochemical deposition, and belongs to the technical field of TGVs. According to the method, the filling quality of the TGV through hole is remarkably improved, the void ratio is reduced, and the packaging reliability is improved; magnetic field assistance and gradient pulse electroplating processes are adopted, so that the electroplating efficiency is improved, and the production period is shortened; meanwhile, due to nanostructure modification and the design of the TiN transition layer, the adhesive force between metal and the hole wall of the glass is enhanced, and the stability of the overall structure is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of TGV, and in particular to a TGV through-hole filling method based on magnetic field assisted electrochemical deposition. Background Art

[0002] In the field of 3D packaging technology, vertical connection between chips through through-silicon vias (TGV) has become an important way to improve integration and performance. However, TGV technology faces a series of complex challenges in practical applications, which directly affect the quality and reliability of packaging.

[0003] First, non-uniform via filling is a prominent problem in TGV technology. During the filling process, the inconsistency of metal deposition rate leads to underfilling in some areas, while other areas may be overfilled. This non-uniformity not only affects the electrical performance of the via, but also may cause mechanical stress concentration, thereby reducing the reliability of the package.

[0004] Secondly, residual bubbles in the hole are also a major problem faced by TGV technology. During the filling process, gas may be entrained into the through hole and form bubbles during the metal deposition process. These residual bubbles will weaken the mechanical strength of the through hole and may become a hidden danger in subsequent use.

[0005] Furthermore, poor metal adhesion on the sidewall is also a problem that cannot be ignored in TGV technology. Insufficient metal adhesion on the sidewall of the through hole will cause the metal layer to peel off during subsequent processing or use, thus affecting the electrical connection performance of the through hole.

[0006] In addition, the application of traditional electroplating processes in TGV technology is also affected by ion diffusion limitations. Due to the limited diffusion rate of ions in the electroplating solution, the metal filling efficiency in the through-hole is low and defects are easily formed. These defects, such as pinholes and cracks, will further affect the electrical performance and mechanical strength of the through-hole.

[0007] In summary, although TGV technology has great application potential in the field of 3D packaging, the challenges it faces are also very severe. It is necessary to further develop new processes to overcome these difficulties and achieve more efficient and reliable 3D packaging. Summary of the invention

[0008] The technical problem to be solved by the present invention is: to overcome the shortcomings of the prior art and provide a TGV through-hole filling method based on magnetic field-assisted electrochemical deposition, which significantly improves the filling quality of the TGV through-hole, reduces the void ratio, and improves the reliability of the package; the magnetic field-assisted and gradient pulse electroplating processes adopted improve the electroplating efficiency and shorten the production cycle; at the same time, the nanostructure modification and the design of the TiN transition layer enhance the adhesion between the metal and the glass hole wall and improve the stability of the overall structure.

[0009] The technical solution of the present invention is:

[0010] The TGV through-hole filling method based on magnetic field assisted electrochemical deposition comprises the following steps:

[0011] S1 pretreatment: Reactive ion etching (RIE) technology is used to etch the inner wall of the glass through hole;

[0012] S2 deposition of transition layer: using atomic layer deposition (ALD) to cover the etched hole wall with a TiN transition layer;

[0013] S3 Magnetic Field Assisted Electrochemical Deposition: Electrochemical deposition is performed on the hole wall using a magnetic field assisted electrochemical deposition device, and the electroplating solution used is a copper sulfate solution or a nickel sulfate solution; the magnetic field assisted electrochemical deposition device includes an electroplating tank, in which the electroplating solution and the glass are placed, and the electroplating tank is provided with an electroplating solution inlet and an electroplating solution outlet, and the electroplating solution inlet is connected to an electroplating solution constant temperature device, and two groups of Helmholtz coils are also provided in the electroplating tank, one group of Helmholtz coils is horizontally arranged, and the other group of Helmholtz coils is vertically arranged;

[0014] During the electrochemical deposition process, the direction of the magnetic field is adjusted by adjusting the Helmholtz coil. The specific operation is as follows:

[0015] Stage 1: Instead of passing current through the vertically arranged Helmholtz coil, pass current through the horizontally arranged Helmholtz coil, and control the current direction and current density to 10-20 mA / cm 2 , making the magnetic field vertically downward; the higher current density provides enough energy to prompt the metal ions to quickly form crystal nuclei on the surface of the pore wall, and the vertically downward magnetic field direction further guides the metal ions to move to the bottom of the pore wall, accelerating the nucleation rate at the bottom;

[0016] Phase 2: The magnetic field rotates by alternately passing current through one or both sets of Helmholtz coils and controlling the direction of the current. When current is passed through both sets of Helmholtz coils at the same time, the current density of the two sets of Helmholtz coils is the same, both 5-10mA / cm 2 Moderate current density ensures the stability of deposition, and the rotation of the magnetic field can disrupt the deposition direction of metal ions, prevent the growth of dendrites, and make metal deposition more uniform;

[0017] Stage 3: Instead of passing current through the horizontally arranged Helmholtz coil, pass current through the vertically arranged Helmholtz coil, and control the current direction and current density to 1-3 mA / cm 2 , making the magnetic field direction horizontal; low current density can slow down the deposition rate, and the horizontal magnetic field direction can make the metal ions deposit evenly in the horizontal direction, thereby leveling the surface and obtaining a high-quality filling effect.

[0018] Under the action of the magnetic field, positively charged metal ions will be subjected to a Lorentz force perpendicular to their direction of movement and the direction of the magnetic field, thereby changing the movement trajectory of the ions, achieving directional migration, and improving the transmission efficiency of the ions in the hole. In the present invention, the vertical magnetic field in the initial filling stage allows the metal ions to move preferentially to the bottom of the through hole, which can promote the deposition of metal ions at the bottom of the hole wall; and in the later stage, the horizontal magnetic field can make the metal ions evenly distributed in the horizontal direction, avoiding excessive deposition of metal ions at the top of the through hole.

[0019] The present invention utilizes the synergistic effect of magnetic field and electrochemistry: the movement path of ions is regulated by an external magnetic field, breaking through the traditional diffusion restrictions and realizing bottom priority filling; nanoscale transition layer design: the TiN transition layer has both conductivity and barrier properties to prevent metal diffusion to the glass substrate; dynamic process parameter matching: real-time coordinated adjustment of magnetic field direction and current density to solve the filling problem of high aspect ratio through holes (>10:1); dynamic adjustment of magnetic field direction: the vertical magnetic field in the initial stage promotes bottom deposition, and the horizontal magnetic field in the later stage suppresses excessive thickness of the top.

[0020] Preferably, in step S1, the specific operation of the etching process is: placing the glass substrate in a reaction chamber of a reactive ion etching device, evacuating the chamber to a vacuum degree of 10 -4 -10 -6 Pa, CF4 / O2, SF6 / O2 or CHF3 / O2 mixed gas is introduced. At a radio frequency power of 150-250W, the mixed gas forms a plasma, in which the active free radicals react physically and chemically with the atoms on the glass surface, etching away some glass atoms and forming a nano-scale roughness of 50-200nm on the inner wall of the glass through-hole, thereby increasing the contact area between the subsequent deposited metal and the glass hole wall and improving the adhesion.

[0021] Preferably, in the mixed gas, the volume ratio of CF4 to O2 is 3:1, the volume ratio of SF6 to O2 is 4:1, and the volume ratio of CHF3 to O2 is 2:1.

[0022] Preferably, the specific operation of step S2 is: placing the glass substrate into the reaction chamber of the atomic layer deposition equipment, and successively introducing the Ti precursor and the N precursor in an alternating gas pulse manner, the Ti precursor chemically adsorbs on the surface of the pore wall to form a single atomic layer, and the N precursor reacts with the adsorbed Ti to grow a TiN film layer by layer. TiN has good electrical conductivity and can promote electron transmission. At the same time, its dense structure can effectively block the diffusion of metal ions to the glass substrate.

[0023] Preferably, in step S2, the thickness of the TiN transition layer is 2-5 nm.

[0024] Preferably, in step S3, the electroplating liquid constant temperature device comprises a storage tank, and an electric heating device and a temperature sensor are arranged in the storage tank.

[0025] Preferably, in step S3, the electroplating tank is provided with a vacuum pump.

[0026] Preferably, in step S3, a transparent observation window is provided on the electroplating tank.

[0027] Preferably, in step S3, the electroplating time of stage one is 25-35 min, the electroplating time of stage two is 15-30 min, and the electroplating time of stage three is 20-25 min.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] The TGV through-hole filling method based on magnetic field assisted electrochemical deposition of the present invention significantly improves the filling quality of the TGV through-hole, reduces the void ratio, and improves the reliability of the package. The magnetic field assisted and gradient pulse electroplating processes adopted improve the electroplating efficiency and shorten the production cycle. At the same time, the nanostructure modification and the design of the TiN transition layer enhance the adhesion between the metal and the glass hole wall and improve the stability of the overall structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 It is a schematic structural diagram of the magnetic field assisted electrochemical deposition device of the present invention including an electroplating tank.

[0031] Figure 2 It is a front view of two groups of Helmholtz coils of the present invention.

[0032] Figure 3 1 is a side view of two groups of Helmholtz coils of the present invention.

[0033] In the figure, 1. electroplating tank; 101. electroplating solution outlet; 2. electroplating solution constant temperature device; 3. Helmholtz coil; 4. vacuum pump; 5. observation window. DETAILED DESCRIPTION

[0034] In order to enable persons skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention.

[0035] like Figure 1 As shown, the magnetic field assisted electrochemical deposition device used in the following embodiments includes an electroplating tank 1, in which the electroplating solution and the glass are placed, and the electroplating tank 1 is provided with an electroplating solution inlet and an electroplating solution outlet 101, and the electroplating solution inlet is connected to the electroplating solution constant temperature device 2, and the electroplating tank 1 is also provided with two groups of Helmholtz coils 3 (such as Figure 2-3 As shown in FIG. 1 , one group of Helmholtz coils 3 is arranged horizontally, and one group of Helmholtz coils 3 is arranged vertically. The constant temperature device 2 for the electroplating liquid includes a storage tank, in which an electric heating device and a temperature sensor are arranged. In addition, the electroplating tank 1 is provided with a vacuum pump 4 and a transparent observation window 5.

[0036] Example 1

[0037] The TGV through-hole filling method based on magnetic field assisted electrochemical deposition in this embodiment includes the following steps:

[0038] S1 pretreatment: Place the alkali-free aluminoborosilicate glass substrate into the RIE etching chamber and evacuate to 10 -5 Pa, RIE etching was performed on the glass substrate, and a CF4 / O2 mixed gas with a volume ratio of 3:1 was introduced. At a radio frequency power of 200W, a roughness of 150nm was formed on the inner wall of the glass through hole.

[0039] S2 deposition of transition layer: the glass substrate is placed in the ALD reaction chamber, and the Ti precursor TDMAT and the N precursor NH3 are introduced in an alternating gas pulse manner. The Ti precursor chemically adsorbs on the surface of the pore wall to form a single atomic layer, and the N precursor reacts with the adsorbed Ti to grow a TiN film layer by layer, and finally a 3nm thick TiN transition layer is obtained, and the resistivity of the TiN transition layer is <200μΩ·cm.

[0040] S3 Magnetic Field Assisted Electrochemical Deposition

[0041] Electrochemical deposition was performed on the hole wall using a magnetic field-assisted electrochemical deposition device, and the electroplating solution used was a 0.8 mol / L copper sulfate solution.

[0042] During the electrochemical deposition process, the direction of the magnetic field is adjusted by adjusting the Helmholtz coil 3. The specific operation is as follows:

[0043] Stage 1: Instead of passing current through the vertically arranged Helmholtz coil 3, current is passed through the horizontally arranged Helmholtz coil 3, and the current direction and current density are controlled to be 15 mA / cm 2 , make the magnetic field vertically downward, and the electroplating time is 30min;

[0044] Phase 2: By alternately passing current to one or both of the Helmholtz coils 3 and controlling the direction of the current, the magnetic field rotates 45° every 5 minutes, thereby rotating between 0° and 180°. When current is passed to both of the Helmholtz coils 3 at the same time, the current density of the two Helmholtz coils 3 is the same, both 8 mA / cm 2 , the electroplating time is 20min;

[0045] Stage 3: Instead of passing current to the horizontally arranged Helmholtz coil 3, pass current to the vertically arranged Helmholtz coil 3, and control the current direction and current density to 2 mA / cm 2 , make the magnetic field direction horizontal, and the electroplating time is 20 minutes.

[0046] Performance Test:

[0047] Filling quality: The glass through-holes were observed using a scanning electron microscope (SEM), and it was found that the through-holes were filled evenly without obvious voids and defects. The SEM images were analyzed using image processing software, and the filling rate was calculated to be 99.5%, and the void rate was <0.1%, which met the requirements for high-quality filling.

[0048] Adhesion between metal and glass hole wall: The scratch test method was used to test the adhesion between metal and glass hole wall, with the scratching needle load set to 5N and the scratch length set to 5mm. The test results showed that the electroplated Cu metal layer did not peel or fall off during the scratching process, indicating that there was good adhesion between the metal and the glass hole wall. This is due to the nano-scale roughness formed by RIE etching and the effect of the TiN transition layer, which increased the contact area between the metal and the glass and improved the adhesion.

[0049] Conductivity: The resistivity of the filler metal was measured using the four-probe method and the resistivity was 1.7×10 -6 Ω·m, which is comparable to the resistivity of pure copper (1.68×10 -6 Ω·m) are similar, indicating that the filling metal has good conductivity. This is mainly because the TiN transition layer has good conductivity, which promotes electron transmission. At the same time, during the electroplating process, the magnetic field assistance and the gradient pulse electroplating process make the metal deposition uniform, ensuring good conductivity.

[0050] Example 2

[0051] The TGV through-hole filling method based on magnetic field assisted electrochemical deposition in this embodiment includes the following steps:

[0052] S1 pretreatment: Place the alkali-free aluminoborosilicate glass substrate into the RIE etching chamber and evacuate to 10 -5Pa, RIE etching was performed on the glass substrate, and a CF4 / O2 mixed gas with a volume ratio of 3:1 was introduced. At a radio frequency power of 150W, a roughness of 100nm was formed on the inner wall of the glass through hole.

[0053] S2 deposition of transition layer: the glass substrate is placed in the ALD reaction chamber, and the Ti precursor TDMAT and the N precursor NH3 are introduced in an alternating gas pulse manner. The Ti precursor chemically adsorbs on the surface of the pore wall to form a single atomic layer, and the N precursor reacts with the adsorbed Ti to grow a TiN film layer by layer, and finally a 2nm thick TiN transition layer is obtained, and the resistivity of the TiN transition layer is <200μΩ·cm.

[0054] S3 Magnetic Field Assisted Electrochemical Deposition

[0055] Electrochemical deposition was performed on the pore wall using a magnetic field-assisted electrochemical deposition device, and the electroplating solution used was a 0.6 mol / L copper sulfate solution.

[0056] During the electrochemical deposition process, the direction of the magnetic field is adjusted by adjusting the Helmholtz coil 3. The specific operation is as follows:

[0057] Stage 1: Instead of passing current through the vertically arranged Helmholtz coil 3, current is passed through the horizontally arranged Helmholtz coil 3, and the current direction and current density are controlled to be 10 mA / cm 2 , make the magnetic field vertically downward, and the electroplating time is 25min;

[0058] Phase 2: By alternately passing current to one or both of the Helmholtz coils 3 and controlling the direction of the current, the magnetic field rotates 45° every 4 minutes, thereby rotating between 0° and 180°. When current is passed to both of the Helmholtz coils 3 at the same time, the current density of the two Helmholtz coils 3 is the same, both 6 mA / cm 2 , the electroplating time is 16min;

[0059] Stage 3: Instead of passing current to the horizontally arranged Helmholtz coil 3, current is passed to the vertically arranged Helmholtz coil 3, and the current direction and current density are controlled to be 1.5 mA / cm 2 , make the magnetic field direction horizontal, and the electroplating time is 20 minutes.

[0060] Performance Test:

[0061] Filling quality: The glass through-holes were observed using a scanning electron microscope (SEM), and it was found that the through-holes were filled evenly without obvious voids and defects. The SEM images were analyzed using image processing software, and the filling rate was calculated to be 99.2%, and the void rate was <0.2%, which met the requirements for high-quality filling.

[0062] Adhesion between metal and glass hole wall: The adhesion between metal and glass hole wall was tested by scratch test method, with the scratching needle load set to 4N and the scratch length set to 4mm. The test results showed that the electroplated Cu metal layer did not peel or fall off during the scratching process, indicating that the metal and glass hole wall had good adhesion.

[0063] Conductivity: The resistivity of the filler metal was measured using the four-probe method and the resistivity was 1.8×10 -6 Ω·m, which is comparable to the resistivity of pure copper (1.68×10 -6 Ω·m) is similar, indicating that the filling metal has good conductivity.

[0064] Example 3

[0065] The TGV through-hole filling method based on magnetic field assisted electrochemical deposition in this embodiment includes the following steps:

[0066] S1 pretreatment: Place the alkali-free aluminoborosilicate glass substrate into the RIE etching chamber and evacuate to 10 -5 Pa, RIE etching was performed on the glass substrate, and a SF6 / O2 mixed gas with a volume ratio of 4:1 was introduced. At a radio frequency power of 250W, a roughness of 200nm was formed on the inner wall of the glass through hole.

[0067] S2 deposition of transition layer: the glass substrate is placed in the ALD reaction chamber, and the Ti precursor TDMAT and the N precursor NH3 are introduced in an alternating gas pulse manner. The Ti precursor chemically adsorbs on the surface of the pore wall to form a single atomic layer. The N precursor reacts with the adsorbed Ti to grow a TiN film layer by layer, and finally a 5nm thick TiN transition layer is obtained. The resistivity of the TiN transition layer is <180μΩ·cm.

[0068] S3 Magnetic Field Assisted Electrochemical Deposition

[0069] Electrochemical deposition was performed on the pore wall using a magnetic field-assisted electrochemical deposition device, and the electroplating solution used was a 1 mol / L copper sulfate solution.

[0070] During the electrochemical deposition process, the direction of the magnetic field is adjusted by adjusting the Helmholtz coil 3. The specific operation is as follows:

[0071] Stage 1: Instead of passing current through the vertically arranged Helmholtz coil 3, current is passed through the horizontally arranged Helmholtz coil 3, and the current direction and current density are controlled to be 20 mA / cm 2 , make the magnetic field vertically downward, and the electroplating time is 35min;

[0072] Phase 2: By alternately passing current to one or both of the Helmholtz coils 3 and controlling the direction of the current, the magnetic field rotates 45° every 6 minutes, thereby rotating between 0° and 180°. When current is passed to both of the Helmholtz coils 3 at the same time, the current density of the two Helmholtz coils 3 is the same, both 6 mA / cm 2 , the electroplating time is 24min;

[0073] Stage 3: Instead of passing current to the horizontally arranged Helmholtz coil 3, current is passed to the vertically arranged Helmholtz coil 3, and the current direction and current density are controlled to be 2.5 mA / cm 2 , make the magnetic field direction horizontal, and the electroplating time is 25 minutes.

[0074] Performance Test:

[0075] Filling quality: The glass through-holes were observed using a scanning electron microscope (SEM), and it was found that the through-holes were filled evenly without obvious voids and defects. The SEM images were analyzed using image processing software, and the filling rate was calculated to be 99.6%, and the void rate was <0.08%, which met the requirements for high-quality filling.

[0076] Adhesion between metal and glass hole wall: The adhesion between metal and glass hole wall was tested by scratch test method, with the scratching needle load set to 6N and the scratch length set to 6mm. The test results showed that the electroplated Cu metal layer did not peel or fall off during the scratching process, indicating that the metal and glass hole wall had good adhesion.

[0077] Conductivity: The resistivity of the filler metal was measured using the four-probe method and the resistivity was 1.65×10 -6 Ω·m, which is comparable to the resistivity of pure copper (1.68×10 -6 Ω·m) is similar, indicating that the filling metal has good conductivity.

[0078] Example 4

[0079] The TGV through-hole filling method based on magnetic field assisted electrochemical deposition in this embodiment includes the following steps:

[0080] S1 pretreatment: Place the alkali-free aluminoborosilicate glass substrate into the RIE etching chamber and evacuate to 10 -5 Pa, RIE etching was performed on the glass substrate, and a CHF3 / O2 mixed gas with a volume ratio of 2:1 was introduced. At a radio frequency power of 200W, a roughness of 150nm was formed on the inner wall of the glass through hole.

[0081] S2 deposition of transition layer: the glass substrate is placed in the ALD reaction chamber, and the Ti precursor TDMAT and the N precursor NH3 are introduced in an alternating gas pulse manner. The Ti precursor chemically adsorbs on the surface of the pore wall to form a single atomic layer, and the N precursor reacts with the adsorbed Ti to grow a TiN film layer by layer, and finally a 3nm thick TiN transition layer is obtained, and the resistivity of the TiN transition layer is <200μΩ·cm.

[0082] S3 Magnetic Field Assisted Electrochemical Deposition

[0083] Electrochemical deposition was performed on the pore wall using a magnetic field-assisted electrochemical deposition device, and the electroplating solution used was a 0.5 mol / L nickel sulfate solution.

[0084] During the electrochemical deposition process, the direction of the magnetic field is adjusted by adjusting the Helmholtz coil 3. The specific operation is as follows:

[0085] Stage 1: Instead of passing current through the vertically arranged Helmholtz coil 3, current is passed through the horizontally arranged Helmholtz coil 3, and the current direction and current density are controlled to be 15 mA / cm 2 , make the magnetic field vertically downward, and the electroplating time is 30min;

[0086] Phase 2: By alternately passing current to one or both of the Helmholtz coils 3 and controlling the direction of the current, the magnetic field rotates 45° every 5 minutes, thereby rotating between 0° and 180°. When current is passed to both of the Helmholtz coils 3 at the same time, the current density of the two Helmholtz coils 3 is the same, both 7 mA / cm 2 , the electroplating time is 20min;

[0087] Stage 3: Instead of passing current to the horizontally arranged Helmholtz coil 3, pass current to the vertically arranged Helmholtz coil 3, and control the current direction and current density to 2 mA / cm 2 , make the magnetic field direction horizontal, and the electroplating time is 20 minutes.

[0088] Performance Test:

[0089] Filling quality: The glass through-holes were observed using a scanning electron microscope (SEM), and it was found that the through-holes were filled evenly without obvious voids and defects. The SEM images were analyzed using image processing software, and the filling rate was calculated to be 99.3%, and the void ratio was <0.15%, which met the requirements for high-quality filling.

[0090] Adhesion between metal and glass hole wall: The adhesion between metal and glass hole wall was tested by scratch test method, with the scratching needle load set to 5N and the scratch length set to 5mm. The test results showed that the electroplated Ni metal layer did not peel or fall off during the scratching process, indicating that the metal and glass hole wall had good adhesion.

[0091] Conductivity: The resistivity of the filler metal was measured using the four-probe method and the resistivity was 7.8×10 -6 Ω·m, which is in line with the conductive properties of nickel metal filling.

[0092] Example 5

[0093] The TGV through-hole filling method based on magnetic field assisted electrochemical deposition in this embodiment includes the following steps:

[0094] S1 pretreatment: Place the borosilicate glass substrate into the RIE etching chamber and evacuate to 10 -5 Pa, RIE etching was performed on the glass substrate, and a CF4 / O2 mixed gas with a volume ratio of 3:1 was introduced. At a radio frequency power of 180W, a roughness of 120nm was formed on the inner wall of the glass through hole.

[0095] S2 deposition of transition layer: the glass substrate is placed in the ALD reaction chamber, and the Ti precursor TDMAT and the N precursor NH3 are introduced in an alternating gas pulse manner. The Ti precursor chemically adsorbs on the surface of the pore wall to form a single atomic layer. The N precursor reacts with the adsorbed Ti to grow a TiN film layer by layer, and finally a 4nm thick TiN transition layer is obtained. The resistivity of the TiN transition layer is <190μΩ·cm.

[0096] S3 Magnetic Field Assisted Electrochemical Deposition

[0097] Electrochemical deposition was performed on the pore wall using a magnetic field-assisted electrochemical deposition device, and the electroplating solution used was a 0.7 mol / L copper sulfate solution.

[0098] During the electrochemical deposition process, the direction of the magnetic field is adjusted by adjusting the Helmholtz coil 3. The specific operation is as follows:

[0099] Stage 1: Instead of passing current to the vertically arranged Helmholtz coil 3, current is passed to the horizontally arranged Helmholtz coil 3, and the current direction and current density are controlled to be 13 mA / cm 2 , so that the magnetic field is vertically downward, and the electroplating time is 28 minutes;

[0100] Phase 2: By alternately passing current to one or both of the Helmholtz coils 3 and controlling the direction of the current, the magnetic field rotates 45° every 4.5 minutes, thereby rotating between 0° and 180°. When current is passed to both of the Helmholtz coils 3 at the same time, the current density of the two Helmholtz coils 3 is the same, both 7 mA / cm 2 , the electroplating time is 18min;

[0101] Stage 3: Instead of passing current to the horizontally arranged Helmholtz coil 3, current is passed to the vertically arranged Helmholtz coil 3, and the current direction and current density are controlled to be 1.8 mA / cm 2 , make the magnetic field direction horizontal, and the electroplating time is 20 minutes.

[0102] Performance Test:

[0103] Filling quality: The glass through-holes were observed using a scanning electron microscope (SEM), and it was found that the through-holes were filled evenly without obvious gaps and defects. The SEM images were analyzed using image processing software, and the filling rate was calculated to be 99.4%, and the void ratio was <0.12%, which met the requirements for high-quality filling.

[0104] Adhesion between metal and glass hole wall: The adhesion between metal and glass hole wall was tested by scratch test method, with the scratching needle load set to 5N and the scratch length set to 5mm. The test results showed that the electroplated Cu metal layer did not peel or fall off during the scratching process, indicating that the metal and glass hole wall had good adhesion.

[0105] Conductivity: The resistivity of the filler metal was measured using the four-probe method and the resistivity was 1.75×10 -6 Ω·m, which is comparable to the resistivity of pure copper (1.68×10 -6 Ω·m) is similar, indicating that the filling metal has good conductivity.

[0106] Comparative Example 1

[0107] The TGV through-hole filling method of Comparative Example 1 comprises the following steps:

[0108] S1 pretreatment: The glass substrate is placed in the RIE etching chamber without strict vacuum treatment, a lot of impurity gas remains in the chamber, and the glass substrate is not subjected to RIE etching treatment;

[0109] S2 is the same as in Example 1;

[0110] S3 electrochemical deposition: The electroplating solution used was 0.8 mol / L copper sulfate solution, and a constant current density of 5 mA / cm 2 The electroplating time is 90 min, and no magnetic field is applied during the electroplating process.

[0111] Performance Test:

[0112] Filling quality: The filling rate is only 80%, the void ratio reaches 8%, and there are a lot of unfilled areas and defects. This is because the presence of impurity gases caused by insufficient vacuum and the lack of etching treatment lead to uneven electroplating process.

[0113] Adhesion between metal and glass hole wall: In the scratch test, when the needle load is 1N and the scratch length is 2mm, the metal layer will obviously fall off and the adhesion is extremely poor.

[0114] Conductivity: Due to discontinuous filling, the resistivity measurement is unstable and the average resistivity is much higher than the normal range.

[0115] Comparative Example 2

[0116] The TGV through-hole filling method of Comparative Example 2 comprises the following steps:

[0117] S1 pretreatment: Place the glass substrate into the RIE etching chamber and evacuate to 10 -3 Pa, RIE etching was performed on the glass substrate, and a CF4 / O2 mixed gas with a volume ratio of 3:1 was introduced. At a radio frequency power of 200W, a roughness of 150nm was formed on the inner wall of the glass through hole.

[0118] S2 does not perform transition layer deposition;

[0119] S3 is the same as in Example 1.

[0120] Performance Test:

[0121] Filling quality: The filling rate is 92%, the void rate is 3%, and there are many voids and defects. This is because the vacuum degree of the etching chamber is too low and the impurity content is high, which affects the etching and electroplating effects.

[0122] Adhesion between metal and glass hole wall: In the scratch test, when the needle load was 3N and the scratch length was 3mm, the metal layer began to partially fall off and the adhesion was not as good as that in Example 1.

[0123] Conductivity: Since no TiN transition layer is formed to promote electron transfer and insufficient vacuum may lead to a decrease in the quality of metal deposition, the resistivity increases to 2.2×10 -6 Ω·m.

[0124] Comparative Example 3

[0125] The difference from Example 1 is that S1 pretreatment: the glass substrate is placed in the RIE etching chamber and evacuated to 10 -5 Pa, the glass substrate is not subjected to RIE etching.

[0126] Performance Test:

[0127] Filling quality: The filling rate is 91% and the void rate is 4.5%. This is because the RIE etching process was not performed, the inner wall of the glass through hole is smooth, the contact area between the metal and the glass hole wall is small, and there are few metal ion attachment sites, which results in uneven metal deposition during the filling process, insufficient filling in many areas, and more voids and defects.

[0128] Adhesion between metal and glass hole wall: In the scratch test, when the stylus load was 3.5N and the scratch length was 4mm, the metal layer began to partially fall off. This is because the lack of nano-scale roughness formed by etching cannot effectively increase the contact area between the metal and the glass, resulting in a significant decrease in the adhesion between the metal and the glass hole wall, and the adhesion is not as good as that in Example 1.

[0129] Conductivity: measured using the four-probe method, the resistivity is about 1.9×10 -6 Ω·m. Due to the discontinuous filling and the presence of many gaps, the electron transmission is greatly hindered, resulting in poor conductivity and increased resistivity.

[0130] Comparative Example 4

[0131] The difference from Example 1 is that in step S3, the treatment of stage 1 is not performed, and the treatment of stage 2 is performed directly, and the electroplating time of stage 3 is 50 minutes.

[0132] Performance Test:

[0133] Filling quality: The filling rate is 93% and the void rate is 3%. This is because the first stage of electrochemical deposition is not carried out, there is no vertical magnetic field to promote the bottom priority deposition, the bottom metal deposition is insufficient, and although it can be supplemented in the subsequent stage, it is difficult to completely make up for the bottom filling defects, making the overall filling not dense enough and there are many tiny gaps.

[0134] Adhesion between metal and glass hole wall: In the scratch test, when the stylus load was 4N and the scratch length was 4.5mm, the metal layer began to partially fall off. This is because the absence of stage 1 affects the nucleation and deposition of the metal at the bottom, destroying the good combination of the metal and the glass hole wall from the bottom, reducing the overall adhesion, and the adhesion is not as good as that of Example 1.

[0135] Conductivity: Resistivity is about 1.78×10 -6 Insufficient bottom filling increases the resistance of electron transfer. Although the metal deposited in the subsequent stage can conduct electricity, the poor filling at the bottom still affects the overall conductive performance, making the resistivity higher than that in Example 1.

[0136] Comparative Example 5

[0137] The difference from Example 1 is that in step S3, the electroplating time of stage 1 is 50 minutes, followed by the operation of stage 3, and the operation of stage 2 is not performed.

[0138] Performance Test:

[0139] Filling quality: The filling rate is 94% and the void rate is 2.2%. This is because the second stage operation is not performed during electrochemical deposition, and the magnetic field rotation cannot be used to disrupt the deposition direction of metal ions, which is prone to dendrite growth. Dendrite growth leads to uneven metal deposition, excessive growth in some areas, and insufficient filling in some areas, which ultimately affects the filling quality and causes a certain amount of voids.

[0140] Adhesion between metal and glass hole wall: In the scratch test, when the scratching needle load was 4.5N and the scratch length was 5mm, the metal layer began to partially fall off. This is because the presence of dendrites makes the contact between the metal and the glass hole wall not tight and smooth, reducing the adhesion between the two. The falling phenomenon occurs under a smaller scratching needle load, and the adhesion is not as good as that of Example 1.

[0141] Conductivity: Resistivity is about 1.75×10 -6 The uneven filling caused by dendrite growth makes electrons encounter more obstacles when transmitting inside the metal, resulting in increased resistance and slightly lower conductivity than Example 1.

[0142] Comparative Example 6

[0143] The difference from Example 1 is that in step S3, the electroplating time of stage 1 is 50 minutes, followed by stage 2, but stage 3 is not performed.

[0144] Performance Test:

[0145] Filling quality: The filling rate is 92% and the porosity is 3.5%. This is because the electrochemical deposition does not perform the third stage operation, and the horizontal magnetic field cannot be used to level the surface. The metal ions on the top continue to deposit and accumulate too thickly, while the bottom may not be completely filled, which reduces the overall filling quality and increases the porosity.

[0146] Adhesion between metal and glass hole wall: In the scratch test, when the stylus load was 3.8N and the scratch length was 4mm, the metal layer began to partially fall off. The excessively thick metal deposition on the top produced a large stress, which destroyed the adhesion balance between the metal and the glass hole wall, causing the metal layer to fall off easily under a small external force, and the adhesion was not as good as that in Example 1.

[0147] Conductivity: Resistivity is about 1.85×10 -6The structure with too thick top and insufficient filling at the bottom seriously affects the uniform transmission of electrons in the entire filling metal, increases the resistance of electron transmission, and makes the resistivity significantly higher than that of Example 1.

Claims

1. A TGV through-hole filling method based on magnetic field assisted electrochemical deposition, characterized in that: The following steps are involved: S1 pretreatment: Reactive ion etching technology is used to etch the inner wall of the glass through hole; S2 deposition of transition layer: using atomic layer deposition to cover the etched hole wall with a TiN transition layer; S3 Magnetic field assisted electrochemical deposition: Electrochemical deposition is performed on the hole wall using a magnetic field assisted electrochemical deposition device, and the electroplating solution used is a copper sulfate solution or a nickel sulfate solution; the magnetic field assisted electrochemical deposition device comprises an electroplating tank (1), the electroplating solution and the glass are placed in the electroplating tank (1), the electroplating tank (1) is provided with an electroplating solution inlet and an electroplating solution outlet (101), the electroplating solution inlet is connected to an electroplating solution constant temperature device (2), and two groups of Helmholtz coils (3) are also arranged in the electroplating tank (1), one group of Helmholtz coils (3) is arranged horizontally, and the other group of Helmholtz coils (3) is arranged vertically; During the electrochemical deposition process, the direction of the magnetic field is adjusted by adjusting the Helmholtz coil (3), and the specific operation is as follows: Stage 1: Instead of passing current through the vertically arranged Helmholtz coil (3), current is passed through the horizontally arranged Helmholtz coil (3), and the current direction and current density are controlled to be 10-20 mA / cm 2 , so that the magnetic field is vertically downward; Phase 2: By alternately passing current through one or both of the Helmholtz coils (3) and controlling the direction of the current, the magnetic field is rotated. When current is passed through both of the Helmholtz coils (3), the current density of the two Helmholtz coils (3) is the same, both being 5-10 mA / cm 2 ; Stage 3: Instead of passing current through the horizontally arranged Helmholtz coil (3), current is passed through the vertically arranged Helmholtz coil (3), and the current direction and current density are controlled to be 1-3 mA / cm 2 , making the magnetic field direction horizontal.

2. The TGV through-hole filling method based on magnetic field assisted electrochemical deposition according to claim 1, characterized in that: In step S1, the specific operation of the etching process is: placing the glass substrate in the reaction chamber of the reactive ion etching equipment, evacuating the vacuum to a vacuum degree of 10 -4 -10 -6 Pa, CF4 / O2, SF6 / O2 or CHF3 / O2 mixed gas is introduced, and a roughness of 50-200nm is formed on the inner wall of the glass through hole at a radio frequency power of 150-250W.

3. The TGV through-hole filling method based on magnetic field assisted electrochemical deposition according to claim 2, characterized in that: In the mixed gas, the volume ratio of CF4 to O2 is 3:1, the volume ratio of SF6 to O2 is 4:1, and the volume ratio of CHF3 to O2 is 2:

1.

4. The TGV through-hole filling method based on magnetic field assisted electrochemical deposition according to claim 1, characterized in that: The specific operation of step S2 is: placing the glass substrate into the reaction chamber of the atomic layer deposition equipment, and successively introducing the Ti precursor and the N precursor in an alternating gas pulse manner, the Ti precursor chemically adsorbs on the surface of the pore wall to form a single atomic layer, and the N precursor reacts with the adsorbed Ti to grow a TiN film layer by layer.

5. The TGV through-hole filling method based on magnetic field assisted electrochemical deposition according to claim 1, characterized in that: In step S2, the thickness of the TiN transition layer is 2-5 nm.

6. The TGV through-hole filling method based on magnetic field assisted electrochemical deposition according to claim 1, characterized in that: In step S3, the electroplating liquid constant temperature device (2) comprises a storage box, in which an electric heating device and a temperature sensor are arranged.

7. The TGV through-hole filling method based on magnetic field assisted electrochemical deposition according to claim 1, characterized in that: In step S3, the electroplating tank (1) is provided with a vacuum pump (4).

8. The TGV through-hole filling method based on magnetic field assisted electrochemical deposition according to claim 1, characterized in that: In step S3, a transparent observation window (5) is provided on the electroplating tank (1).

9. The TGV through-hole filling method based on magnetic field assisted electrochemical deposition according to claim 1, characterized in that: In step S3, the electroplating time of stage 1 is 25-35 minutes, the electroplating time of stage 2 is 15-30 minutes, and the electroplating time of stage 3 is 20-25 minutes.

Citation Information

Cited By

  • Deposition method of metal seed layer in TGV metallization and magnetron sputtering equipment

    CN121575364A

  • Method for depositing a metal seed layer in tgv metallization and magnetron sputtering apparatus

    CN121575364B

  • Large-size glass plate level TGV through hole pre-moistening control system, method and device

    CN122147470A